Implementation of Authentication Systems on Hotspot Network Users to Improve Computer Network Security - Ellen Dolan; Riya Widayanti (International Institute for Advanced Science & Technology (IIAST), 2022)
Because of the growing number of apps that use client servers, both desktop and WEB applications, each user must learn a large number of user ids and passwords, because each application requires authentication in order to use it for security reasons. Furthermore, the development of network media, both wired and wireless, is accelerating. In the scenarios stated above, RADIUS (Remote Authentication Dial-In User Service) technology is required since the RADIUS approach allows a user to utilize a single user id to access several applications, both desktop and web-based. The RADIUS protocol may be used with both wired and wireless media.